A retrospective case series of rupture uterus during five years period at a rural medical college in West Bengal, India - Patra, Kajal Kumar; Mandal, Apurba; Chattopadhyay, Shibram; Biswas, Arunava; Majumder, Siddhartha (Asian Journal of Medical Sciences, 2021)
Background: Rupture of the uterus carries major risk of maternal and perinatal morbidity and mortality especially in the developing world. Aims and Objectives: This study aims to identify retrospectively the risk factors leading to uterine rupture through case series and to determine the feto-maternal outcome of such serious clinical condition. Material and Methods: A retrospective study was done at Bankura Sammilani Medical College, Bankura, West Bengal, India from January 2014 to December 2018 to observe the incidence, aetiology, management and complications with maternal and foetal mortality and morbidity associated with rupture of the uterus in pregnant women at different gestational periods. The data were obtained from the case record section of the hospital. All rupture uterus cases were included excluding the dehiscence of scarred uterus. Results: Twenty-one cases of Rupture Uterus were documented out of total delivery of 43,323 mothers in five years. There was a single maternal death and 15 (71.42 %) unbooked cases. Previous mode of delivery was found to be vaginal in 5 cases (23.8%). Most of the incidences of rupture uterus were scarred uterus (previous caesarean section and repaired uterus) 16 cases (76.19%), prolonged / obstructed labour 4 cases (19%), inductionof labour 1 (4.76%) and spontaneous rupture 1 (4.76%). Most cases were multiparous; site of rupture was in lower uterine segment in 18 cases (85.7%), fundal rupture 2 cases (9.52%) and left lateral 3 cases (14.2%). Bladder injury was in 1 case (4.76 %). Total abdominal hysterectomy was performed in 2 cases (9.52%) andsubtotal hysterectomy were done in 15 cases (71.4%); repair of the ruptured uterus wasperformed in 4 cases (19%). Fever and wound infections were present in 5 cases (23. 8%). Maternal death 1(4.76%) and 3 babies survived with perinatal mortality 18 (85.7%). Conclusion: Mandatory antenatal care, prompt diagnosis and safe instrumental delivery may change the rupture uterus incidences.